HLA‐DQB1*03:01:34, a novel allele, which has arisen by silent mutation in codon 87. (22nd November 2016) - Zhou, D.; Jin, S.‐Z.; Zou, H.‐Y.
Abstract : HLA‐DQB1*03:01:34 has one nucleotide change from HLA‐ DQB1*03:01:01 at nucleotide 357 bp where C>A in exon 2.